War or peace in Sri Lanka : an in-depth account of the current quest for peace - Dissanayaka, T. D. S. A. (Colombo : Swastika (Pvt.) Ltd., 1995)
An account of the current politics and ethnic conflict in Sri Lanka.
Keywords: Sri Lanka -- Politics and government -- 1978-; Sri Lanka -- Ethnic relations